Juridical Analysis of the Socialization Process in the Formation of Village Regulations Based on Law No. 6 Of 2014 in Tanjung Pasir Village - Muhammad Faiz Siregar; Muhammad Viki Ardi (SEAN Institute, 2025)
The socialization of Law Number 6 of 2014 concerning Villages, held in Tanjung Pasir Village, Pangkalan Susu District, Langkat Regency, aimed to strengthen community understanding of their rights and obligations in the process of drafting Village Regulations (Perdes). This activity focused on environmental conservation issues, particularly the protection of mangrove ecosystems as part of efforts to build sustainable villages. Involving 17 participants from the community, village officials, and environmental partners of the Sumatran Elephant Foundation (Yagasu), this activity was carried out in a participatory and deliberative manner. The legal approach used in this outreach refers to the principle of participatory democracy, as stipulated in Article 68 of Law No. 6 of 2014 and Article 96 of Law No. 12 of 2011 concerning the Formation of Legislation. Yagasu's presence as a partner strengthens the substance of village regulations through ecological education and legal assistance, which encourages the integration of environmental protection into local legal norms. Through village deliberations, participants not only receive material but also actively convey aspirations and questions related to their position as legal subjects in the formulation of Village Regulations. The findings of this activity demonstrate that targeted and facilitated public participation can produce village regulations that are normatively legal and ecologically just. This outreach demonstrates that the formation of village-level law depends not only on formal legality but also on social and ecological legitimacy built through collaboration between the community, village government, and non-state actors. Thus, this activity model makes an important contribution to the practice of village governance and environmental law, and is an effective approach to supporting democratic and sustainable village development.